Excess cervical cancer screening smears: Any benefit? A retrospective cohort in Alsace, France. (June 2017) - Thiery, Alicia; Akladios, Cherif; Fender, Muriel; Severac, François; Baldauf, Jean-Jacques
Objectives: Although cervical cancer screening guidelines in France recommend a smear test every three years, many physicians order more regular screening. We aimed to assess the benefits or harms of shorter intervals between screenings, both for women and public health. Methods: For a retrospective cohort of women aged 25–65 who had two normal smears and at least one additional smear, data were sourced from a regionally organized cervical cancer screening programme in France, with follow-up for nine years. Based on the interval between the second and third smear, two groups were formed; the first comprised overscreened women (interval <24 months), and the second of 'correctly' screened women (interval between 24 and 42 months). The primary outcome was cervical intraepithelial neoplasia 2 or worse (CIN2+); secondary outcomes were cervical cancers and CIN1 lesions. Results: Among 63, 821 women, CIN2+ incidence rate per 10, 000 women per year was 14.5 for 40, 350 overscreened women, and 11.5 for 23, 471 correctly screened women. Age-adjusted relative risk was 1.22[1.02; 1.46]. We found no significant difference for cancer (RR = 1.39; 95%CI = [0.60; 3.61]), but did find additional CIN1 in the overscreened group (RR = 2.09; 95%CI = [1.76; 2.51]). Conclusions: A shorter interval between smears has a low benefit for CIN2+ lesion detection, which may not help avoid cancer. The excess number of CIN1 detected by overscreening may cause needless risk and excess costs due to overtreatment.